On Philosophical Meaning of Negative Terms in Laozi: Revolving around “Truthful Words Seem Contrary” (正言若反) - Yiming Wang (Religions, 2022)
Negative terms are widespread in the text of Laozi; however, our understanding of their field, form and philosophical meaning is still unclear. In this paper, I intend to argue that the theoretical meaning of these terms first needs to be understood in terms of the proposition “Truthful words seem contrary”. In this proposition, “contrary” is the accurate meaning of negative terms. I demonstrate that the essence of the “contrary” lies in the critical reaction of xuande (dark virtue) to mingde (brilliant virtue), which is the traditional highest value. Thus, dark virtue is the theoretical foundation of the “contrary” because it is the new highest value. The “contrary” manifests itself in two forms: intuitive words (including adjectives and nouns), which are reflective, and negative words (including negative adverbs and verbs). Intuitive words represent the highest value or Being by means of the states and beings in the empirical world (I make use of the ontological difference between Being and being made by Heidegger, and so I maintain the capitalization of Being). In contrast, negative words more clearly distinguish the highest value or Being from secular values and beings in negative sentences. According to a further analysis of the relationship between affirmative and negative sentences, the latter is the universal expression of the former. All of these propositions reveal a philosophical possibility in which the diverse ways and values of the existence of all beings are affirmed and fulfilled.